AS DIRETRIZES CURRICULARES DE ARTE DO ESTADO DO PARANÁ: UMA ANÁLISE DOS FUNDAMENTOS E DA GESTÃO DO ENSINO DE MÚSICA EM PONTA GROSSA/PR (2003-2010) - Stori, Regina (2011)
This work presents an analysis of the foundations of the Curriculum Guidelines of the State of Paraná (DCE) and of the management of the art/music teaching proposed in such document within the context of the city of Ponta Grossa/PR. The aims of this research include: to analyse the theoretical bases used in the Art Curriculum Guidelines of the State of Paraná; to historicise public policies for art/music teaching implemented in Paraná from 1990 to 2010; to investigate the conditions under which the Art Curriculum Guidelines of the State of Paraná were implemented, taking into account that such conditions were provided by the State Department of Education (SEED); to know what concepts of art teaching the interviewed managers hold; to find out how the DCE are managed in specific educational entities (Art Coordination Division of the Regional Centre of Ponta Grossa and management staff of some schools in the city of Ponta Grossa) This research is based on the historical and dialectical materialism, focusing on the categories of contradiction and totality (CURY, 1989; KOSIK, 1976; LUKÁCS, 1978) in order to apprehend the dialectics of both the formulation of policies proposed by the State and its management and interpretation in different educational entities. Some concepts, understood in relation to the object addressed herein, were studied and called into question in the data analysis based on some authors: State, public policies, policy management (GRAMSCI, 1991; BOBBIO, 1997; CARNOY, 1984; TAVARES, 2004; VIEIRA, 2007); art and art teaching (FIGUEIREDO, 2009, 2010; PENNA, 1995, 2001a, 2007, 2008b; SUBTIL, 2008, 2009a, 2009b; VÁZQUEZ, 1978). Data collection was carried out through the analysis of official documents related to the research object, as well as through semi-structured interviews with a teacher who took part in the policy formulation and is in charge of its management, a teacher who worked as an art consultant at the SEED, the coordinator teacher of the Art section of the Regional Education Centre of Ponta Grossa, and five principals of public schools in Ponta Grossa. The combination of the collected data with the theoretical references shows that: a) contradictions implicit in the historical movement whereby art was included in school education are expressed not only in the document text but also in the subjects‟ concepts and interpretations; b) the management of the Guidelines reflects the concepts of art and art/music teaching adopted by the subjects of the different educational entities; c) even though there are some conditions proposed by the State for the implementation of the policy referred to in the document, the concrete reality – in which the lack of material and human resources and the persistence of historically established concepts of art and art/music teaching are quite evident – doesn‟t contribute to putting into effect a proposal that represents an advance in terms of contents and concepts of art and art/music teaching.